Network Topology Impacts on Repair Cost in Distributed Storage System with Network Coding - Qin, Shengwei; Li, Zhong (2018 IEEE International Conference on Electronics and Communication Engineering (ICECE), 2018)
The paper proposed a problem that the network topology impacts on the repair cost over a distributed storage system with network coding. Contrary to the general network model, the tandem network model exists a link between the adjacent nodes. To repair one failed node over the two network models, it might cost a small price over the tandem network model compared to the general network model. The paper concluded that the optimal repair cost in the tandem network is obtained no matter where the position of the failed node is. Meanwhile, the minimum repair cost was obtained over the tandem network and the general network model. Finally, the experiments of minimum repair cost over one type of real world network model (such as WSNs) showed that the network topology has a significant impact on the repair cost as well as the theoretical support in the paper.